STRATEGI PENINGKATKAN KESEJAHTERAAN MASYARAKAT NELAYAN DI KABUPATEN KEPULAUAN SELAYAR - Darmawansyah, Rony; Usman, Jaelan; Wahid, Nur (Universitas Muhammadiyah Makassar, 2024)
The purpose of this study is to determine Reductive Strategies and Persuasive Strategies in improving the welfare of fishermen in Pasimarannu District. The method used in this study is qualitative research, data collection techniques in this study are observation, interviews, and documentation. The results of this study indicate that the Pasimarannu District government's efforts to improve the welfare of fishermen are by implementing a Reductive Strategy which is carried out in community empowerment activities through socialization counseling machine repair training Furthermore, the Persuasive Strategy is a form of government effort to persuade the community to make the desired changes, this strategy involves counseling activities, providing assistance, and building facilities and infrastructure. In implementing the strategy there are several supporting and inhibiting factors. Supporting factors that influence the implementation of the Reductive Strategy, namely, the presence of trained personnel in the field of training and empowering fishing communities, the availability of infrastructure, and government cooperation with educational institutions,